Analisis Penerapan Manajemen Waktu Terhadap Efektivitas Kinerja Karyawan Toko Uwais Donat Praya - Ridho Algifari; Noni Antika Khairunnisah; Andi Pranata; Muhammas Azim (Journal of Public Sector Financial Management, 2025)
This research aims to determine the effect of time management on the effectiveness of the performance of Uwais donut shop employees. This research uses qualitative research with the data collection methods used are surveys and interviews. The population and sample are Uwais Donut employees. This research was conducted on January 4 2024 at 18.00-finish at the Uwais Donut shop located in Praya. Central Lombok. Uwais donut is a food shop that produces and sells food such as donuts, bread, cakes, desserts. Uwais donuts also provides various kinds of accompanying drinks such as iced coffee, Milo ice, coconut ice, mixed ice, and the drink that is currently viral, namely chocolate ice pack. The price also varies, starting from IDR 6,000 - IDR 35,000 depending on each type. The location of this donut shop is in a strategic location, namely on Jalan Sultan Hasanudin Leneng, Praya. The conclusion obtained is that employees must have the ability to manage time well, this influences performance effectiveness.